(untitled) (Research, Society and Development, 2023)
Based on the importance of monitoring and qualifying the evaluation processes, building the profile of competencies of the HP, and on the perception that the use of Reliable Professional Activities (APCs) associated with the matrix of competencies in-service teaching confer robustness to the training of Professionals for the Unified Health System, the present study, based on the methodology of documentary research, proposes APCs for the evaluation of Resident Health Professionals (PSR) of the Multiprofessional Residency Program in Adult Mental Health of the Higher School of Health Sciences. This structuring proposal, based on the analysis of documents related to the Residency Programs in the professional area of health and the Brazilian Psychiatric Reform, is justified by the search for qualification of the said Program, in line with the policies of the Ministry of Health for professional training in the area of health with the legislation establishing these Residences. The APCs were structured in eight sections that detail the entire process of elaboration, understanding, execution and evaluation of the PSR during the two years of permanence in the respective Program. It is concluded that improving the profile of postgraduate graduates through a Residency in Mental Health that is attentive to the needs of the population will occur through attention to the principles of the Brazilian Psychiatric Reform, progressively promoting improvements in the services of the Psychosocial Care Network.